2011
DOI: 10.1111/j.1528-1167.2011.03217.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and comedication on lamotrigine clearance, tolerability, and efficacy

Abstract: SUMMARYPurpose: To compare pharmacokinetics, tolerability, and efficacy of lamotrigine (LTG) in older versus younger adults. Methods: We studied 686 adult outpatients seen at our center over 5 years. We compared apparent clearance (CL) of LTG in the youngest (16-36 years; n = 247) and oldest (55-92 years; n = 155) tertiles. We analyzed oneyear retention for younger and older adults newly started on LTG, frequency of adverse effects causing intolerability, and rates of specific adverse effects. We also investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…14 In this study, no effects of age on pharmacokinetics were evident with lamotrigine or oxcarbazepine, but there was a large variability within the groups and too few patients in some of the subgroups for oxcarbazepine to demonstrate a significant effect. 22 The choice of comedication in various age groups may affect the results regarding the impact of age. 14,18,19 Previous studies give contradictory results regarding lamotrigine in children.…”
Section: Discussionmentioning
confidence: 99%
“…14 In this study, no effects of age on pharmacokinetics were evident with lamotrigine or oxcarbazepine, but there was a large variability within the groups and too few patients in some of the subgroups for oxcarbazepine to demonstrate a significant effect. 22 The choice of comedication in various age groups may affect the results regarding the impact of age. 14,18,19 Previous studies give contradictory results regarding lamotrigine in children.…”
Section: Discussionmentioning
confidence: 99%
“…The 1-year retention for lamotrigine was comparable in older (78.1%, 121/155) and younger (72.4%, 179/247) adults in spite of the fact that younger adults tolerate lamotrigine better than older adults do. Some patients may benefit from high serum levels of lamotrigine (Arif et al, 2011). A multi-center retrospective observational study of the efficacy, tolerability, and retention rate of gabapentin use in children showed that gabapentin was well tolerated, with 55% of patients remaining on treatment beyond 1 year.…”
Section: Retention Ratesmentioning
confidence: 99%
“…The only study, except our study in adults, that describes similar outcomes in triple therapy with CBZ, is Hachad et al, Perucca and Böttiger et al who mentioned that the effect of VPA was fully compensated in the presence of CBZ. Arif et al described decreased LTG clearance in combinations with VPA, +CBZ+VPA, and +TPM+VPA compared to monotherapy. Unfortunately, the difference from respective bitherapy was not statistically significant, probably due to low sample numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The information about seizure type was not given in 655 (50%) request forms. The influence of the concomitant AED therapy was evaluated using the weight‐adjusted hourly apparent clearance (CL) that was calculated according to the following formula:CLfalse[mLfalse/hfalse/kgfalse]=LTG_dose0.333333em[mg/kg/d]×10.333333emd/240.333333emhplasma_concentration0.333333em[mg/L]×10.333333emL/10000.333333emmL…”
Section: Methodsmentioning
confidence: 99%